Pregnancy with Systemic Lupus Erythematosus- An Enigma- A Case Report - B S Gamini; Sangamesh Mathapati; Aruna Biradar; Preeti Patil; Shobha Shirgur; S R Bidri (Wolters Kluwer Medknow Publications, 2020)
Introduction: Systemic Lupus Erythematosus (SLE) is one of the most common autoimmune disorders that affect women during their childbearing years. Lupus exacerbation during pregnancy occurs in about 20-30% of pregnant lupus patients. SLE increases the risk of spontaneous abortion, intrauterine death, preeclampsia, FGR and preterm birth. Case Report: A 23 year old Primi mother with 6 months of amenorrhea reported with complains of skin and oral lesions and breathlessness since 20 days. She was hemodynamically stable, had a malar rash, macular skin lesions and generalized edema. Systemic examination showed hepatomegaly with ascites and pleurisy signs. Urine microscopy showed 15 to 20 pus cells/HPF. Echo cardiograph showed pericardial effusion. A provisional diagnosis of Pregnancy with SLE was made. Antinuclear antibody and Anti smith Ab was positive. She was started on oral steroids and HCQS. One month later the patient presented with maculopapular lesions all over the body. There was a history of discontinuation of drugs for a short duration. The dermatologist opined it as ROWELL syndrome. The obstetric evaluation showed SIUG of 33 weeks with anhydromnios with Doppler changes with steroid prophylaxis, Emergency LSCS was done. A live female baby of weight 2.7 kg was extracted and was shifted to NICU for preterm care. Post-operative period was uneventful except for full-thickness gaping of LSCS wound. Both mother and baby were discharged after 2wks. Conclusion: Pregnancy with SLE is a tricky medical challenge needing multidisciplinary approach and intensive care. Advancing technology and a better understanding of the disease have improved outcomes in lupus pregnancies.